Simulating the Effects of GATT-UR/WTO on the Philippine Economy - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1997)
The GATT/WTO may affect the Philippine economy in three ways: through changes in tariff structure resulting from the country's commitment in the Uruguay Round, through the expansion of world trade as developed and less developed countries adjust their protection structures and through the changes in the prices of tradable goods as both DC's and LDC's realign their trade and non-trade barriers. This paper simulates the possible effects of these developments in the local economy. In particular, this paper aims to determine whether the impact is favorable at the macroeconomic level and whether it is progressive in terms of income distribution. To simulate the impact of these changes, a computable general equilibrium model of the Philippine economy called the APEX model is utilized.
Keywords: 330; computable general equilibrium (CGE); agriculture sector